Exploring the involvement of men who use intimate partner violence in social work education: Student and service user views. (November 2021) - Jury, Rebecca; Boxall, Kathy
There is growing international interest in service user involvement in social work education, but some service user groups are more likely to be included than others. This article explores the possibility of involving male service users who use intimate partner violence in Australian social work education. The article describes focus groups conducted separately with social work students and men who use intimate partner violence, which explored participants' understandings of lived experience, service user involvement in social work education and the place of men who use intimate partner violence in the social work academy. The findings suggest it may be possible to involve previously excluded service user groups in social work education.